Green Building Best Practices in Achieving Energy and Environmental Sustainability - Sapuan, Noraina Mazuin; Haron, Nazatul Faizah; Vija Kumaran, Vikniswari; Saudi, Nur Surayya; Ridzuan, Abdul Rahim (Environmental Management and Sustainable Development, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In the construction and building industry, sustainable development is becoming a powerful force for economic, social, and environmental gains with fewer negative consequences for the environment. It is essential to establish green and sustainable practices in the building and construction industry in order to improve energy efficiency, particularly by utilising the newest green technologies. As a result, the study’s objectives are to first investigate the most relevant practices to be used for green building employment; second, evaluate the benefits produced by the execution of green building; and third, analyse the best practices of green building characteristics. The findings of this study showed that green buildings developed using energy-efficient systems and implementing sustainable practices can reduce energy consumption, as well as lower the cost of operating and maintaining these buildings in the long term. Meanwhile, the government’s role is essential to attracting more participants in implementing sustainable practices in the construction and building sector, especially through more stringent regulations and appealing incentives.